Analysing open-source images in forensic anthropology - Cobham, L.; Harris, Michael; Márquez-Grant, Nicholas (Asociación Española de Antropología y Odontología Forense, 2023)
Forensic scientists, including forensic anthropologists, are increasingly being called on to comment on images depicting human remains taken from public domains. The current unprecedented scale of digital material available online and on social media regarding the conflict in Ukraine and previously in Syria, and the various logistical difficulties for verifying alleged human rights abuses and crimes that may have occurred there, suggest the need for further knowledge and understanding of the utility of open-source images in the field of forensic anthropology. This study surveyed 10 conflict-related open-source images among professionals with varying backgrounds in forensic anthropology to assess their usefulness for forensic anthropological investigative purposes. Qualitative and quantitative methods were used. The results revealed that most participants were able to provide diagnostic interpretations from open-source images and considered their analyses useful to varying degrees. Minimal differences were observed in comparing responses with experience and/or qualifications. The study revealed that a greater consideration must be given to the forensic analysis of open-source images, particularly given the increasing demand for forensic anthropological expertise and current technological developments.
Keywords: Open Source Intelligence; Human Remains; Human Rights Investigations; False Flags; Disinformation; Conflict; Images